National intellectual capital influence on innovation and sustainability - Valter Vairinhos; Matos, F.; Matos, A. (Intellectual capital management as a driver of sustainability: Perspectives for organizations and society, 2019)
Sustainability is nowadays a main objective of society. It is not enough to struggle for economic development; this development and innovation that supports it must have in due count people happiness and ecological restrictions. Given the global pressure on innovation capabilities and sustainability of ecosystems, many studies try to measure the economic development of countries, linking it to investment in Intellectual Capital. In this context, intangible assets management and, specifically, Intellectual Capital (IC) and Knowledge Management (KM), became generally acknowledged Innovation factors. This chapter is about the possible causal relations between the concepts National Intellectual Capital (NIC), Innovation (INOV), Competitivity (COMP) and Sustainability (SUST). Seeing IC as a creative potential for new ideas and concepts, it is generally believed that Innovation, being the potential of transformation of new ideas and concepts into real products and services, is strongly influenced (caused) by IC: after all, the innovation must be preceded by the idea. In the same way, the efficiency of transformation of new ideas into products seems to heavily depend on new ideas related with industrial production, work organization and management, which seems to justify the notion that it makes sense to assume causal effects between IC and INOV and IC and COMP. Although IC, INOV and COMP have specific pathways in each country, it makes also sense to assume that all these variables affect, negatively or positively, the wellbeing of future generations. This chapter is a quantitative research on the validity of these theoretical hypotheses. Having this target in mind, an exploratory model for those relations was built and estimated using observational available open data from international sources for each one off the mentioned variables. The main supporting methodologies employed were descriptive multivariate data analysis techniques and PLS path modelling. In terms of originality, this empirical study aims to contribute to stimulate the emergence of data driven discussions about the factors that determine the sustainability of countries, aiming the formulation of policies and strategic planning.